Ekonomska analiza prava in distributivna pravičnost - Šošić, Miha (LeXonomica, 2021)
Economic analysis of law and distributive justice. The author examines certain aspects of the relationship between law and economics as an interdisciplinary study and distributive justice as a problem of legal philosophy. The author tries to define certain connections between the problems of distributive justice and the economic analysis of law by examining the Coase theorem. The goal is to point out how some theories of law and economics directly or indirectly touch the subject of distributive justice. It is through this that the limitations of law and economics become evident. It is the author’s opinion that law and economics form a subsidiary study that can provide mainly a secondary analysis of legal norms from the viewpoint of their efficiency. Therefore law and economics cannot substitute legal philosophy which should remain the primary focus when forming the legal system as well as through the process of adoption and use of legal norms. Povzetek. Članek obravnava nekatere povezave med ekonomsko analizo prava, ki kot interdisciplinarna veda preučuje pravne norme z vidika ekonomske teorije, in vprašanjem distributivne pravičnosti, ki jo umeščamo na področje filozofije prava. Avtor poskuša definirati nekatere stične točke med problemi distributivne pravičnosti in teorijami ekonomske analize prava na primeru Coasovega teorema in pri tem opozoriti, kako se nekatere teorije ekonomske analize prava posredno ali neposredno dotikajo vprašanj distribucije dobrin in bremen v družbi. Namen avtorja je opozoriti ne nektere omejitve ekonomske analize prava. Po avtorjevem mnenju je namen ekonomske analize prava kot pomožne vede zlasti sekundarna analiza pravnih norm z vidika njihove učinkovitosti, zato ekonomska analiza prava ne more nadomestiti ukvarjanja s pravno filozofskimi problemi, ki morajo biti v ospredju pri ustvarjanju pravnega sistema ter sprejemanju in uporabi pravnih norm.